Laser patterning of boron carbon nitride electrodes for flexible micro-supercapacitor with remarkable electrochemical stability/capacity - Karbhal, Indrapal; Basu, Aniruddha; Patrike, Apurva; Shelke, Manjusha V. (Carbon, 2021)
High performance, all solid-state planar micro-supercapacitor (MSC) with interdigitated Boron carbon Nitride (BCN) electrodes are fabricated via fast, scalable laser patterning technique. Heteroatom doping desirably enhances the electrochemical activity of carbon electrodes. This BCN based micro-supercapacitor showed comparatively very high specific capacitance of 72 mFcm(-2) at a current density of 0.15 mAcm(-2). Even at a high current density of 1 mAcm(-2) device showed specific capacitance as high as 17 mFcm(-2). It has demonstrated excellent electrochemical stability when tested up to 80000 cycles without any sign of further decay in capacity/efficiency. This device showed stable capacity even after bending at 150 degrees angle, for 1500 times during cycling showing remarkable flexibility. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: BCN; Co-doping; Energy storage; Flexible; Laser patterning; Micro-supercapacitor

Progress and potential of electrospinning-derived substrate-free and binder-free lithium-ion battery electrodes - Joshi, Bhavana; Samuel, Edmund; Kim, Yong-il; Yarin, Alexander L.; Swihart, Mark T.; Yoon, Sam S. (Chemical Engineering Journal, 2022)
Carbon nanofibers derived from electrospun precursors show great promise for electronic applications owing to their flexibility, conductivity, high surface area, and open structure. The integration of metal oxides and sulfides in carbon nanofibers, rather than using them with other binders, eliminates many problems caused by poor adhesion, nanomaterial agglomeration, excess mass contributed by inactive binders, and low conductivity of embedded active materials. The engineering of electrospun fibers with novel morphologies, such as core-shell, hollow, or porous structures, and the use of decorated carbon nanofibers (e.g., by electrodeposition or co precipitation) are discussed in this review. Representative schematic illustrations of the lithium-storage mechanism for these binder-free electrodes are presented. We describe how the electrospinning technique can offer a cost-effective strategy for fabrication of lightweight lithium-ion batteries with high capacity and excellent bendability. This review presents the fascinating morphologies of these specially designed carbon nanofiber electrodes, which enhance the electrochemical performance of metal oxides and sulfides, illustrating their enormous potential for use in wearable electronic devices and hybrid electric vehicles.
Keywords: Carbon nanofibers; Co-axial; composites; core-shell; electrospinning; Flexible

Review of recent progress in electrospinning-derived freestanding and binder-free electrodes for supercapacitors - Joshi, Bhavana; Samuel, Edmund; Kim, Yong-il; Yarin, Alexander L.; Swihart, Mark T.; Yoon, Sam S. (Coordination Chemistry Reviews, 2022)
The versatile electrospinning technique is scalable and suitable to fabricate highly conducting freestanding carbon nanofiber composite electrodes for energy storage devices. Freestanding/flexible electrodes hold enormous potential for use in wearable electronic devices. Carbon-yielding polymers and the optimal use of sacrificial polymers, metal oxides, and sulfides retain the flexibility and enhance the surface area and pseudocapacitance of electrodes. Both as-prepared electrospun fibers and carbonized nanofibers are compatible with surface decoration via various chemical and electrochemical routes. Metal oxides/sulfides with various morphologies, such as nanocones and nanosheets, can be grown on the carbon nanofibers or on the as-prepared electrospun fibers using chemical synthesis methods such as electro-deposition, hydrothermal processes, and chemical impregnation to enhance the pseudocapacitance of the electrodes. Similarly, the deposition of metal organic frameworks on as-prepared electrospun fibers embellishes these fibers with nanostructures of specific morphologies such as dodecahedral and spindle-shaped structures. Under optimal conditions, these morphologies do not hamper the flexibility of the fibers, and binders are not required to retain them or maintain the electrode integrity. The engineering of electrodes with various morphologies and process parameters is presented systematically. Electrospinning-derived electrodes that have demonstrated significant electrochemical performance are highlighted and critically analyzed, and the energy storage mechanisms of these supercapacitors are described in detail. (C) 2022 Elsevier B.V. All rights reserved.
Keywords: Carbon nanofibers; Co-axial; composites; core-shell; electrospinning; Flexible; Porous; supercapacitor